The analytics of New Keynesian Phillips curves - Alfred Maußner (Universität Augsburg, Institut für Volkswirtschaftslehre, 2010)
This paper introduces the reader into the apparatus behind the popular New Keynesian Phillips (NKPC) curve. It derives several log-linear versions of this curve and recursive formulations of the Calvo-Yun price staggeringmodel that is behind this curve. These formulations can be used for higher-order approximations of the NKPC or for implementations that use other non-linear solution techniques, as, e.g., projection methods.
urn:nbn:de:bvb:384-opus4-711110
Keywords: E31; E37; E43; E47; 330; New-Keynesian Phillips Curve; New-Keynesian Phillips Curve; Theorie